Highly efficient MoOx-free semitransparent perovskite cell for 4 T tandem application improving the efficiency of commercially-available Al-BSF silicon. Issue 1 (December 2018) - Ramos, F. Javier; Jutteau, Sebastien; Posada, Jorge; Bercegol, Adrien; Rebai, Amelle; Guillemot, Thomas; Bodeux, Romain; Schneider, Nathanaelle; Loones, Nicolas; Ory, Daniel; Broussillou, Cedric; Goaer, Gilles; et al.
Abstract In this work, the fabrication of MoOx -free semitransparent perovskite solar cells (PSC) with Power Conversion Efficiencies (PCE) up to 15.7% is reported. Firstly, opaque PSCs up to 19.7% were fabricated. Then, the rear metal contact was replaced by a highly transparent and conductive indium tin oxide (ITO) film, directly sputtered onto the hole selective layer, without any protective layer between Spiro-OMeTAD and rear ITO. To the best of our knowledge, this corresponds to the most efficient buffer layer-free semitransparent PSC ever reported. Using time-resolved photoluminescence (TRPL) technique on both sides of the semitransparent PSC, Spiro-OMeTAD/perovskite and perovskite/TiO2 interfaces were compared, confirming the great quality of Spiro-OMeTAD/perovskite interface, even after damage-less ITO sputtering, where degradation phenomena result less important than for perovskite/TiO2 one. Finally, a 4-terminal tandem was built combining semitransparent PSC with a commercially-available Aluminium Back Surface Field (Al-BSF) silicon wafer. That silicon wafer presents PCE = 19.52% (18.53% after being reduced to cell size), and 5.75% once filtered, to generate an overall 4 T tandem efficiency of 21.18% in combination with our champion large semitransparent PSC of 15.43%. It means an absolute increase of 1.66% over the original silicon wafer efficiency and a 2.65% over the cut Si cell.